Dobutamine stress cardiac MRI is safe and feasible in pediatric patients with anomalous aortic origin of a coronary artery (AAOCA). (1st July 2021) - Doan, Tam T.; Molossi, Silvana; Sachdeva, Shagun; Wilkinson, James C.; Loar, Robert W.; Weigand, Justin D.; Schlingmann, Tobias R.; Reaves-O'Neal, Dana L.; Pednekar, Amol S.; Masand, Prakash; Noel, Cory V.
Abstract: Background: Risk stratification in anomalous aortic origin of a coronary artery (AAOCA) is challenged by the lack of a reliable method to detect myocardial ischemia. We prospectively studied the safety and feasibility of Dobutamine stress-cardiac magnetic resonance (DSCMR), a test with excellent performance in adults, in pediatric patients with AAOCA. Methods: Consecutive DSCMR from 06/2014–12/2019 in patients≤20 years old with AAOCA were included. Hemodynamic response and major/minor events were recorded. Image quality and spatial/temporal resolution were evaluated. Rest and stress first-pass perfusion and wall motion abnormalities (WMA) were assessed. Inter-observer agreement was assessed using kappa coefficient. Results: A total of 224 DSCMR were performed in 182 patients with AAOCA at a median age of 14 years (IQR 12, 16) and median weight of 58.0 kg (IQR 43.3, 73.0). Examinations were completed in 221/224 (98.9%), all studies were diagnostic. Heart rate and blood pressure increased significantly from baseline (p < 0.001). No patient had major events and 28 (12.5%) had minor events. Inducible hypoperfusion was noted in 31/221 (14%), associated with WMA in 13/31 (42%). Inter-observer agreement for inducible hypoperfusion was very good (Κ = 0.87). Asymptomatic patients with inducible hypoperfusion are considered high-risk and those with a negative test are of standard risk. Conclusions: DSCMR is feasible in pediatric patients with AAOCA to assess for inducible hypoperfusion and WMA. It can be performed safely with low incidence of major/minor events. Thus, DSCMR is potentially a valuable test for detection of myocardial ischemia and helpful in the management of this patient population. Graphical abstract: Unlabelled Image Highlights: Dobutamine stress CMR has excellent performance in adults with ischemic heart disease. DSCMR with first pass perfusion is safe and feasible in pediatric patients with AAOCA. DSCMR results guide management of AAOCA using shared decision making with families. Most DSCMR after AAOCA surgery were negative and allowed for return to activities.